Analisis Pull Strategy Pada Marketing Public Relations Program BRI Incubator dalam Meningkatkan Kinerja UMKM Go Global - Ria Magdalena, Elisabeth Charoline; Abdurrahman, M. Sufyan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The BRI Incubator program is designed to enhance the capabilities of Micro, Small, and Medium Enterprises (MSMEs) through three primary focus areas: Go-Modern, Go-Digital, and Go-Online. The Go-Modern initiative aims to educate MSMEs on effective product packaging tailored to market demands, thereby increasing competitiveness. The Go-Digital initiative equips MSMEs with the skills to leverage digital platforms and social media for promotional purposes, expanding their market reach. Lastly, the Go-Online initiative empowers MSMEs to market their products via online marketplaces or to develop their own platforms for wider distribution. This research seeks to explore the public relations marketing strategies employed by the BRI Incubator to elevate the performance of the MSMEs under its guidance. Employing a qualitative methodology with a phenomenological approach, the study investigates the experiences and perceptions of program participants. The findings reveal that the success stories of BRI Incubator participants contribute significantly to the development of a strong brand image for the BRI Incubator, thereby enhancing its reputation and effectiveness.